The True Effect of a Lumbar Dural Tear on Complications and Cost. Issue 3 (1st February 2020) - Alluri, Ram; Kang, H. Paco; Bouz, Gabriel; Wang, Jeffrey; Hah, Raymond J.
Abstract : Study Design: Retrospective database analysis. Objective: The aim of this study was to match risk factors for complications in patients who did and did not sustain a dural tear while undergoing posterior lumbar spine surgery and compare local and systemic complications. Summary of Background Data: Current data do not adequately define whether the event of sustaining an isolated dural tear increases the risk for postoperative complications while controlling for other confounding risk factors. Methods: The PearlDiver Database was queried for patients who underwent posterior lumbar spine decompression and/or fusion for degenerative pathology. Patients with and without dural tears were 1:2 matched based on demographic variables and comorbidities. Complications, cost, length of stay (LOS), and readmission rates were analyzed. Results: The 1:2 matched cohort included 9038 patients with a dural tear and 17, 340 patients without a dural tear. All complications assessed were significantly higher in the dural tear group ( P < 0.03). Venothromboembolic (VTE) events occurred in 1.3% of patients with a dural tear and 0.9% of patients without a dural tear (odds ratio [OR] 1.46, P < 0.0001). Meningitis occurred in 25 patients (0.3%) with a dural tear and eight patients (<0.1%) without a dural tear (OR 6.0, P < 0.0001). Patients with a dural tear had 120% higher medical costs, 200% greater LOS, and were two times more likely to be readmitted ( P < 0.0001). Conclusion: Sustaining a dural tear while undergoing posterior lumbar spinal decompression and/or fusion for degenerative pathology significantly increased the risk of complications and increased length of stay, risk of readmission, and overall 90-day hospital cost. Dural tears specifically increased the risk of a VTE complication by 1.46 times and meningitis by six times; these are important complications to have a high degree of suspicion for in the setting of durotomy, as they can lead to significant morbidity for the patient. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textIn a matched cohort, patients who sustained a dural tear demonstrated a significantly increased risk of developing postoperative complications including venothromboembolic events and meningitis. Total cost, readmission rates, and length of stay were also greater in the dural tear group.